2019
DOI: 10.1002/adfm.201808741
|View full text |Cite
|
Sign up to set email alerts
|

Stable α‐CsPbI3 Perovskite Nanowire Arrays with Preferential Crystallographic Orientation for Highly Sensitive Photodetectors

Abstract: All-inorganic metal-halide perovskites CsPbX 3 (X = Cl, Br, I) exhibit higher stability than their organic-inorganic hybrid counterparts, but the thermodynamically instable perovskite α phase at room temperature of CsPbI 3 restricts the practical optoelectronic applications. Although the stabilization of α-CsPbI 3 polycrystalline thin films is extensively studied, the creation of highly crystalline micro/nanostructures of α-CsPbI 3 with large grain size and suppressed grain boundary remains challenging, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 37 publications
0
82
0
Order By: Relevance
“…Previous studies reported that the PVP molecule can stabilize the CsPbI 3 crystal by interacting with the Cs + to change its surface energy state, and a 10% weight ratio yields the optimized results. [ 8,10 ] So we add 10 wt% PVP into the precursor solvent. A vacuum treatment process is necessary before the annealing (Figure S1c, Supporting Information), or the patterned CsPbI 3 will not transfer into the black phase but the yellow phase instead (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that the PVP molecule can stabilize the CsPbI 3 crystal by interacting with the Cs + to change its surface energy state, and a 10% weight ratio yields the optimized results. [ 8,10 ] So we add 10 wt% PVP into the precursor solvent. A vacuum treatment process is necessary before the annealing (Figure S1c, Supporting Information), or the patterned CsPbI 3 will not transfer into the black phase but the yellow phase instead (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous report, the disordered crystallographic growth will contribute to the intensity of (110) plane, so its reduction means a more preferential crystal growth along the desired (100) crystallographic orientation, suggesting the improvement of the film quality. [ 10 ] A control flat film at the 0.6 m concentration is fabricated for comparison. SEM images (Figure S4, Supporting Information) show that the flat film has rough morphology with many grain boundaries, while the nanowire array does not show obvious boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 20,21 ] Random nucleation is a disadvantage in the precise control of crystal locations for device integration. [ 22,23 ] Hence, the controllable growth of high‐quality perovskite single crystals for a device is highly challenging. This significantly hinders the controllable production of high‐performance perovskite single‐crystal devices in arrays for integrated electronic and optoelectronic systems.…”
Section: Figurementioning
confidence: 99%